The Influence of Organizational Culture and Motivation on the Performance of DISKOMLEKAU (Indonesian Air Force Communications and Electronics Service) Employees With the Mediation of Job Satisfaction - Erwan Aprilian; Endang Tjahjaningsih (DINASTI RESEARCH, 2026)
The purpose of this study is to analyze the influence of organizational culture and motivation on the performance of Diskomlekau (the Directorate of Communication and Electronics of the Indonesian Air Force), with job satisfaction as the mediating variable. The study used a quantitative approach with a survey method to collect data from Diskomlekau members. Data analysis techniques used included validity and reliability tests, linear regression, and mediation analysis using the Sobel test to examine the role of job satisfaction in the relationship between independent and dependent variables. The results of the study showed that organizational culture has a positive and significant effect on job satisfaction, with a regression coefficient of 0.999, a t-statistic of 14.582, and an R² of 0.678. Motivation also positively and significantly influenced job satisfaction, with a regression coefficient of 0.944, a t-statistic of 18.599, and an R² of 0.774. Additionally, organizational culture positively and significantly influences performance, with a regression coefficient of 1.173, a t-statistic of 13.132, and an R² of 0.631. Work motivation also positively and significantly influences performance, with a regression coefficient of 1.064, a t-statistic of 14.109, and an R² of 0.663. The results of the mediation test showed that job satisfaction significantly mediated the influence of organizational culture on performance, with a Sobel z-value of 2.869 and a p-value of 0.004. Job satisfaction also significantly mediates the effect of motivation on performance, with a Sobel z-value of 4.212 and a p-value of 0.000. These findings confirm that job satisfaction is an important mechanism in strengthening the influence of organizational culture and motivation on the performance of Diskomlekau members.